EVOLUTION OF DIFFERENT PROGRAMMING LANGUAGES - Cimermanis, Edgars; Grabusts, Pēteris (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2020)
This article is about programming languages, that has improved over time and is still evolving. The goal of this work is to delve into specifics of programming languages and the logic behind they’re evolving. This paper will overlook parts of programming languages to understand, why there is so many of them and how they work.